The Impact of Price, Product Quality, and Brand Image on Vienna Skincare Purchase Decisions Among Bandung University Students - Vira Rohmania Oktaviani; Dadan Abdul Aziz Mubarok (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to find out how Bandung university students' decisions to purchase Vienna skincare products are influenced by brand perception, price, and product quality. Both a survey approach and a quantitative methodology were employed in the investigation. Data from one hundred students who had previously used Vienna skincare products was collected using purposeful sampling. The results demonstrate that brand image has a favorable and significant influence on purchasing decisions (t = 2.433; p = 0.017). Price has a positive and substantial influence (t = 2.172; p = 0.032), while product quality has the biggest impact on purchasing decisions (t = 3.469; p < 0.001). Brand image, price, and product quality have a significant simultaneous influence on purchasing decisions, as indicated by an F-value of 356.917 (p < 0.001). The three independent variables account for 91.8% of the variation in purchase decisions, with other factors not included in this study impacting the remaining 8.2%, according to the coefficient of determination (R2) of 0.918. These findings highlight the importance of maintaining product quality, implementing appropriate pricing strategies, and enhancing brand image to improve purchase decisions among local skincare brands targeting student consumers.